Sosialisasi Budidaya Sistem Aquaponik Dan Praktek Pengolahan Hasil Perikanan Didesa Fadoro Kecamatan Manderehe Kabupaten Nias Barat - Agnes Juwita Dawolo; Angel Sri Ayu Gea; Heppi Kristiani Waruwu; Martin Gulo; Irfan Waruwu; Estin Krisdila Zebua; Ratna Dewi Zebua (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Aquaponics is an integrated farming system that combines fish farming (aquaculture) and soil-less farming (hydroponics) in a recirculating ecosystem. Fish waste is filtered by bacteria and converted into nutrients for the plants, while the plants help maintain water quality for the fish. This community service activity was carried out by student interns through socialization and practice of aquaponic cultivation systems and fishery product processing on June 10, 2025, in Fadoro Village, West Nias. The aquaponic system has proven efficient in utilizing limited land, reducing the use of chemical fertilizers, and producing healthy and environmentally friendly products.